#TITLE_ALTERNATIVE# - EVA RAMADHANIA, GEAVANI
We study the effect of mass transfer in six close binary star evolutions, i.e. SV Cen, V Pup, Z Vul, ? Persei, V356 Sgr, and V367 Cyg. These include changes in the stellar interior structure, energy transport, and how lifetime and evolution track of both components in the system depend on these. Accurate physical and orbital parameter of close binary stars were deduced using PHOEBE (Physics of eclipsing Binaries) package. Modeling the evolution of close binary star was done using the MESA (Modules for Experiments in Stellar Astrophysics) package. The results of six evolutionary models show that (1) the core radius of both stars in each system increased after mass transfer occurred, (2) the hydrogen fraction in the center of mass-gaining star increased so that the helium fraction was reduced during mass transfer, (3) the rate of hydrogen and helium burning in the mass-losing star will reduce while in the mass-gaining star will increase, (4) the increasing of material on the mass-gaining star form a deep convective layer on its surface, but itÃ‚Â’s not always happen (5) in general, both stellar surface show H-deficiency and He-enrichment. The increasing of core radius cause the core density and temperature reduce so that the burning rate in mass-losing star will reduce. The increasing of hidrogen fraction cause the core density and temperature increase so that the burning rate in mass-gaining star will increase. Conservative model seems do not fit for V356 Sgr and V367 Cyg. Therefore, a non-conservative model shall be considered on those close binaries.